2013
DOI: 10.1038/jes.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Urinary iodine concentrations of pregnant women in rural Bangladesh: A longitudinal study

Abstract: Iodine is an essential dietary element required for normal fetal growth and development. We aimed to explore intraindividual and interindividual variations in iodine intake in pregnant women and whether non-dietary factors might influence the intake. Iodine intake was assessed in 271 women, residing in Matlab, rural Bangladesh, by measuring their urinary iodine concentration (UIC) at gestational week (GW) 8, 14, 19, and 30 with inductively coupled plasma mass spectrometry. The women's UIC increased significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…The present study also showed a weak positive association between BMI and UIC, which correlates with previous reports from Bangladesh and Romania [64,65]. A possible explanation could be that pregnant and non-pregnant women with high BMI were consuming higher foods rich in iodine than lean individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The present study also showed a weak positive association between BMI and UIC, which correlates with previous reports from Bangladesh and Romania [64,65]. A possible explanation could be that pregnant and non-pregnant women with high BMI were consuming higher foods rich in iodine than lean individuals.…”
Section: Discussionsupporting
confidence: 90%
“…The present study also showed a weak positive association between BMI and UIC, which correlates with previous reports from Bangladesh and Romania [54,55]. A possible explanation could be that pregnant and non-pregnant women with high BMI were consuming higher foods rich in iodine than lean individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Cadmium, selenium and iodine in urine were measured with inductively coupled plasma mass spectrometry (ICPMS; Agilent 7700×, Agilent Technologies, Tokyo, Japan), equipped with an octopole reaction system, at Karolinska Institutet, Sweden [19, 20]. When measuring cadmium and selenium the urine samples were diluted 1:10 in 1 % nitric acid (prepared from 65 % suprapur, Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%